A History of China-U.S. Relations (1911–1949) - Tao, Wenzhao. author. aut Link
XL, 394 p. 2 illus.
Keywords: This book contains tthe history of China-U.S. Relations (1911–1949), including China-US relations in Early Republican Period, the impact of Versailles Peace Conference and Washington Conference on China-US relations, US support for Northern Warlord Government, the Guangzhou Revolutionary Government, and the Nanjing National Government. During the War of Resistance Against Japanese Aggression, the United States went from neutral to form an alliance with China against Japan. After the end of the War, China and the United States gradually moved toward confrontation. This book also has a brief description of China-US relations from 1784 to 1911.